Photovoltaic Economic Potential For Investment Portfolio In South East Asia - Mohd Ab Halim, Mohd Firdaus; Harun, Mohamad Haniff; Mohd Annuar, Khalil Azha; Azahar, Arman Hadi; Ab Hadi, Nik Azran (Asian Research Publishing Network (ARPN), 2016)
-